PENGARUH METODE SUGESTOPEDIA DAN MOTIVASI BELAJAR TERHADAP KEMAMPUAN MENULIS CERPEN SISWA SMA - Engla Tivana (Jurnal Semantik, 2015)
This study aimed to clarify the effect of the method sugestopedia andhigh motivation and low motivation to learn the ability to write a short storySMA. The population was SMA. Sampling totaled 40 students conducted bypurposive sampling. Questionnaire used to see students' motivation andperformance tests conducted to determine the ability of students to writeshort stories. Analysis and discussion of the data is done in accordance withthe descriptive-analytical study concept experiments. Based on the results ofthe data analysis we can conclude the following four things. First, the abilityto write short stories that taught using methods suggestopedic better thanstudents taught by conventional methods. Second, the ability to write shortstories of students who have high motivation are taught using methodssuggestopedic better than that taught by conventional methods. Third, theability to write short stories of students who have low motivation are taughtusing methods suggestopedic better than that taught by conventionalmethods. Fourth, there is no interaction between learning motivation andlearning methods in affecting students' ability to write short stories.Keywords: method sugestopedia, learning and motivation, short story writing ability